Gender Statistics and Local Governance in China: State Feminist versus Feminist Political Economy Approaches*. (29th January 2016) - Chen, Lanyan
Abstract: Gender statistics provide an essential tool to mainstream gender equality in policymaking through the recognition by government and the public of gender differences in all walks of life. One legacy of feminist movements since the 1990s has been a focus on the challenges women face to effect substantive equality with men. Based on the findings of a project carried out in three districts of Tianjin, this paper identifies a lack of gender statistics in China's statistical system and the resulting negative impacts on local policymaking. The findings point to weaknesses in the Chinese "state feminist" approach to gender statistics, mostly at the level of the central government. From a feminist political economy perspective, the paper argues, policymaking in China is a process built upon centralized statistical reporting systems that serve the senior governments more than local communities. Gender statistics have the potential to enhance local governance in China when policymaking becomes a site of contestation where community activists demand the use of statistics to assist policies that promote equality. 摘要: 性别统计能使政府和大众对各行各界所存在的性别差异得到认识, 并据此成为决策过程中性别平等主流化的一个基本工具。 女权运动自上世纪九十年代以来的一个持久重心是面对要跟男性一起实现实质性平等的种种挑战。本文就天津三个区的一个研究项目的发现表明在中国统计制度中性别统计的缺失以及其对地方决策所造成的负面影响。该项目的发现也指出了 "国家女权主义" 在中国过于集中于中央政府的性别统计的缺陷。本文从女权主义政治经济的角度分析了中国决策过程所建立的统一报表的统计制度是为上级政府而不是为地方社区服务。进而, 只有当决策成为社区活动家要求使用统计来推动有利于平等政策而力争的地域时, 性别统计才将在中国发挥出其提高地方治理的潜力。